Friction in gravitational waves: a test for early-time modified gravity - Pettorino, Valeria; Amendola, Luca (Arxiv, 2015)
Modified gravity theories predict in general a non standard equation for the propagation of gravitational waves. Here we discuss the impact of modified friction and speed of tensor modes on cosmic microwave polarization B modes. We show that the non standard friction term, parametrized by $α_{M}$, is degenerate with the tensor-to-scalar ratio $r$, so that small values of $r$ can be compensated by negative constant values of $α_M$. We quantify this degeneracy and its dependence on the epoch at which $α_{M}$ is different from the standard, zero, value and on the speed of gravitational waves